2018 IEEE Conference on Computational Intelligence in Bioinformatics and Computational Biology (CIBCB) 2018
DOI: 10.1109/cibcb.2018.8404961
|View full text |Cite
|
Sign up to set email alerts
|

Parameter selection for modeling of epidemic networks

Abstract: The accurate modeling of epidemics on social contact networks is difficult due to the variation between different epidemics and the large number of parameters inherent to the problem. To reduce complexity, evolutionary computation is used to create a generative representation of the epidemic model. Previous gains from the use of local, verses global, operators are further explored to better balance exploration and exploitation of the genetic algorithm. A typical parameter study is conducted to test this new lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…A caveat to these findings is that these are slight trends in that the confidence intervals of all PSs within a given profile overlap. These findings correlate with those found in [11] where local toggle performed better on all profiles except profile 8. This provides further evidence that better performance may be achieved if parameters are tuned on a per-profile basis.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…A caveat to these findings is that these are slight trends in that the confidence intervals of all PSs within a given profile overlap. These findings correlate with those found in [11] where local toggle performed better on all profiles except profile 8. This provides further evidence that better performance may be achieved if parameters are tuned on a per-profile basis.…”
Section: Resultssupporting
confidence: 89%
“…In [17] it is demonstrated that swap allowed for better performance than hop for the PM problem. Additionally, [11] establishes that, for most profiles, the best fitness was accomplished when the probability of toggle and local toggle are approximately equal. Therefore, the percentage for swap is zero for both parameter sweeps.…”
Section: B Exp a And B: Local Add And Delete On The Pm Problemmentioning
confidence: 95%
See 2 more Smart Citations
“…The Local THADS-N generative representation [11] will be used in this paper to generate the personal contact networks which then are assessed for performance against the test problems. Existing applications of generative representations include [9], [13], [17].…”
Section: B Generating Personal Contact Networkmentioning
confidence: 99%